"The Place of Solemne Prayer": Intrasettlement Post-and-Trench Mortuary-Ritual Structures in the Precontact Era of Northern Ohio. Issue 1 (2nd January 2020) - Redmond, Brian G.; Traster, Alyssa Davis
ABSTRACT: Most traditional archaeological interpretations of life within late precontact period village sites in the Eastern Woodlands focus primarily on the domestic sphere or ritual activities associated solely with burial features. Yet, ethnohistorical studies reveal that both the domestic and ritual-ceremonial realms were tightly entangled in the lives of indigenous actors during the contact period. A recent reanalysis of a small enclosure and burial precinct at the White Fort site in northern Ohio presents new evidence of ceremonial use and reuse within a large habitation site during the late precontact period (ca. AD 1250–1400). Excavation data reveal how human interment, artifact caching, and layering of colored soils were incorporated in six pit burials arranged around a C-shaped post-and-ditch enclosure. The sequencing of interments and enclosure construction that composed this distinct area show that it served as a hub for burial and ritual behavior over multiple generations of seasonal village occupation.